Biogas Reforming over Al-Co Catalyst Prepared by Solution Combustion Synthesis Method - Manapkhan Zhumabek (Catalysts, 2021)
The results of carbon dioxide reforming of CH4 (model biogas) on catalysts prepared by solution combustion synthesis (SCS) and impregnation of moisture capacity methods are presented. Investigation of the activity of catalysts synthesized from initial mixtures of Co(NO3)2-Al(NO3)3-urea of different compositions was carried out for the production of synthesis-gas, and SCS and traditional incipient wetness impregnation catalyst preparation methods were compared. The methane conversion reached 100%, and the conversion of CO2 increased to 86.2%, while the yield of H2 and CO was 99.2% and 85.4%, respectively, at 900 °C. It was found that CoAl2O4 spinel formation was due to substitution of Al3+ with Co2+ cations. Consequently, CoAl2O4 lattice parameters increased, since the ionic radius of Al3+ (0.51Å) less than Cο2+ (0.72 Å). Advantages of SCS catalysts in comparison with catalysts prepared by the traditional incipient wetness impregnation method in dry reforming of methane were shown. The aim of this work is to develop a new catalyst for the conversion of model biogas into synthesis gas, which will contribute to the organization of a new environmentally friendly, energy-saving production in the future.